A critical review of definitions for exergetic efficiency in reverse osmosis desalination plants. (15th October 2017) - Blanco-Marigorta, A.M.; Lozano-Medina, A.; Marcos, J.D.
Abstract: Different approaches for formulating exergetic efficiency in desalination plants are suggested in literature. In this work these formulations, applied to the reverse osmosis technology, are compared and critically reviewed. As a case study, a reverse osmosis desalination plant in operation has been considered. A key factor is the proper definition of the exergy value of the product and the exergy value of the fuel. In reverse osmosis modules, where chemical separation is carried out, chemical exergy plays also an important role. Another influential issue is the thermodynamic model used in the calculation of the thermodynamic properties. Inappropriate thermodynamic models and ambiguous exergetic efficiency definitions bring confused and contradictory results: negative values of the chemical exergy, exergy production in pumps, or larger irreversibilities in the membranes than in the pumps. The enormous deviations found in the Literature can only be due to different conceptual definitions. In order to clarify these contradictions, this work provides a precise definition for the exergetic efficiency in reverse osmosis desalination plants devices. Highlights: Review and comparison of exergetic efficiency in reverse osmosis desalination plants. Different conceptual definitions lead to enormous deviations. Appropriate seawater thermodynamic properties formulations should be used. A new definition for the fuel and product exergy in the membranes is proposed. Chemical exergy should be taken into account.